1991
DOI: 10.1039/c39910001027
|View full text |Cite
|
Sign up to set email alerts
|

New mechanistic aspects of anodic monofluorination of halogenoalkyl and alkyl phenyl sulphides

Abstract: A unique Pummerer type mechanism via fluorosulphonium ions for anodic monofluorination of sulphides is established by comparing the anodic monofluorination of partially halogenated ethyl phenyl sulphides (1, PhSCH2R; R = CF3, CF2H, CFH2, CF2CI, CCIH2) with their anodic methoxylation; simple alkyl phenyl sulphides 2 bearing no electron-withdrawing group could be monofluorinated anodically in satisfactory yields for the first time when tetrahydrofuran was used as a solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 9 publications
(2 reference statements)
0
14
0
Order By: Relevance
“…On the other hand, we found that a-electron-withdrawing groups promoted the anodic a-fluorination of organosulfur and selenium compounds as shown in [17][18][19][20]. Simonet and co-workers [21] also reported that anodic a-fluorination of alkyl phenyl sulfides was promoted by an electron-withdrawing group on the benzene ring as shown in Scheme 4(b).…”
Section: Introductionmentioning
confidence: 83%
“…On the other hand, we found that a-electron-withdrawing groups promoted the anodic a-fluorination of organosulfur and selenium compounds as shown in [17][18][19][20]. Simonet and co-workers [21] also reported that anodic a-fluorination of alkyl phenyl sulfides was promoted by an electron-withdrawing group on the benzene ring as shown in Scheme 4(b).…”
Section: Introductionmentioning
confidence: 83%
“…Selective electrochemical fluorination to form 42 of phenyl 2,2,2-trifluoroethyl sulfide [74], a-(phenylthio)acetate and related organosulfur compounds, bearing electron withdrawing groups was successful in acetonitrile containing Et 3 NÁ3HF (Scheme 22) [75].…”
Section: Electrochemical Partial Fluorinationmentioning
confidence: 99%
“…293 Electrochemical fluorination of arylsulfides constitutes another transformation that has been extensively studied by several research groups. Early work during the 1990s from the Fuchigami [294][295][296][297][298][299][300][301][302] (Scheme 27) and Laurent 303,304 (Scheme 28) laboratories demonstrated that the introduction of an electronwithdrawing group at the a-position to sulfur had a dramatic influence on the reactions. These a-fluorination transformations were believed to proceed through a Pummerer-type mechanism where the electron-withdrawing group facilitates deprotonation of the a-carbon to produce intermediate 110, thereby promoting fluorination.…”
Section: Anodic Halogenationmentioning
confidence: 99%